An appraisal of the public secondary school libraries in the first district of Manila - Valderrama, Norma R. (Institute of Library Science, University of the Philippines Diliman, 1970)
Studies the facilities and services of the secondary school libraries in Tondo for the school year 1969-70. Findings with regards to their personnel, collections, quarters, furniture and equipment and finances were presented and analyzed. These were then compared and evaluated against existing standards.